Spiritual Personality Education through Wirid Practices in the Syattariyah Order: A Case Study at Islamic Boarding School of Al-Anwar Maron Purworejo - Muzamilatur Rohmah; Mahmud Nasir (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The spiritual crisis associated with modern life underscores the need for alternative character-building approaches capable of addressing inner restlessness and strengthening spiritual resilience. This study aims to examine the formation of congregants’ spiritual personality through the practice of wirid in the Syattariyah Order at Al-Anwar Maron Islamic Boarding School, Purworejo. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three principal dimensions. First, the practice of wirid is implemented through a structured initiation process comprising intention, ritual bathing, a six-unit prayer, fasting, and regular recitation after the Isha and Subuh prayers under the guidance of a mursyid. Second, the practice cultivates spiritual values encompassing tawḥīd, zuhd, maḥabbah, tawakkul, patience, honesty, and sincerity, which are manifested in inner tranquility, humility, sincerity, and closeness to Allah. Third, wirid shapes spiritual personality through four interconnected psychospiritual mechanisms: fostering spiritual awareness, facilitating purification of the soul (tazkiyat al-nafs), promoting holistic character formation, and nurturing inner peace (al-nafs al-muṭmaʾinnah). The study concludes that the Syattariyah practice of wirid at Al-Anwar Maron functions not merely as a religious ritual but as an internalized formative process that enables congregants to develop an adaptive spiritual personality amid the pressures of modern life. These findings contribute to the understanding of Sufi devotional practices as mechanisms of spiritual character formation and offer practical implications for integrating structured spiritual discipline into character education within Islamic boarding schools.